Evaluating rail suicide prevention measures - Ryan, Brendan; Wronska, Urszula; Stevens, Ian (2017)
Many rail safety interventions are implemented without sufficient consideration of the effectiveness of the intervention or the degree to which the intervention has been implemented. This paper describes a programme of work to develop, test and implement a simple framework and associated research tools that can be used by rail staff to collect better data for evaluating the effectiveness of rail suicide prevention measures. Problems that have been encountered in attempting to embed this framework within organisational processes are described.